Design and Implementation of a Telemetry System for Environmental Applications - Aziz, Jabir S.; Hussein, Osama A. (Al-Khwarizmi Engineering Journal, 2019)
The Environmental Data Acquisition Telemetry System is a versatile, flexible and economical means to accumulate data from multiple sensors at remote locations over an extended period of time; the data is normally transferred to the final destination and saved for further analysis. This paper introduces the design and implementation of a simplified, economical and practical telemetry system to collect and transfer the environmental parameters (humidity, temperature, pressure etc.) from a remote location (Rural Area) to the processing and displaying unit. To get a flexible and practical system, three data transfer methods (three systems) were proposed (including the design and implementation) for rural area services, the first method is an RF link which can be used for field applications and rural areas. The other two methods are based on the utilization of packet-switching network (GPRS and Internet networks) to transfer the collected data to the required destination. Remote and Master units which represents the break down of the three proposed system are designed and implemented